Large complex ovarian cyst managed by laparoscopy - Limbachiya, Dipak J.; Chaudhari, Ankit; Agrawal, Grishma P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Complex ovarian cyst with secondary infection is a rare disease that hardly responds to the usual antibiotic treatment. Most of the times, it hampers day to day activities of women. It is commonly known to cause pain and fever. To our surprise, in our case the cyst was large enough to compress the ureter and it was adherent to the surrounding structures. Laparoscopic removal of the cyst was done and specimen was sent for histopathological examination.